A thermodynamic and environmental performance of in-situ gasification of chemical looping combustion for power generation using ilmenite with different coals and comparison with other coal-driven power technologies for CO2 capture. (15th January 2017) - Fan, Junming; Zhu, Lin; Hong, Hui; Jiang, Qiongqiong; Jin, Hongguang
Abstract: Chemical looping combustion (CLC), as "next-generation" CCS, is suggested as the most promising candidate for a long-term implementation of carbon capture. This study is aimed to examine both thermodynamic and environmental performances of ilmenite-based in-situ gasification chemical looping combustion (iG-CLC) power plant with different coals. Besides, comparison with already-achievable coal-feed plants are involved. Thermodynamically, lower oxygen carrier to fuel ratio (ф) is more feasible to obtain autothermal operation in high-rank coal-feed iG-CLC plant. Anthracite-feed iG-CLC power plant obtains the highest net electricity efficiency (46.0%). Approximately more than 10% net electricity efficiency benefits are earned in an iG-CLC power plant (anthracite-based case) compared with that in conventional plants. From environmental aspect, CO2 emission rates for lignite-feed iG-CLC plant amount to be the highest, i.e. 103.05 kg/MW h vs. the lowest bituminous-based case (91.94 kg/MW h). Due to the higher CO and sulfur compounds concentration, the captured CO2 stream in an iG-CLC plant may not be qualified for direct transport, and further pre-transport treatment is required. For anthracite-feed iG-CLC power station, the net NO emission rate ranks the highest (4.14 kg/MW h). By contrast, it has been reduced by 0.07 kg/MW h and 0.28 kg/MW for bituminous and lignite-feed case, respectively. Highlights: Thermodynamic performances of iG-CLC power plants with different coal feedstock are assessed. Environmental assessments of iG-CLC power plants are included. Comparisons between iG-CLC plants and other commercialized coal-feed plants are included.